Cytotoxic Effects of Aminotriles with Bioactive Potential: An Integrative Review - Vieira, Paola da Costa; Cavalcanti, Lettícia Tenório; Almeida, Hélida Maravilha Dantas e Sousa; Sousa Oliveira, Igor de; Ferreira, Sávio Benvindo (Archives of Pharmacy and Pharmaceutical Sciences, 2023)
Aminonitriles are pharmacological-interest bioactive due to their promising antimicrobial and antitumor activity. Since cytotoxicity tests are inherent to the new drug development process, this work aimed to verify reports in the scientific literature on the cytotoxic effects of aminonitriles. The method adopted was an integrative review of works published in the last 10 years in the PubMed, Embase, Web of Science, and Virtual Health Library (VHL) databases. Three articles that matched the selection and eligibility criteria were included in this review. A total of 33 aminonitriles were used in the cytotoxicity experiments, and of the nine molecules based on pyridine, two exerted moderate cytotoxic activity, of the twelve synthesized from benzimidazole, none showed cytotoxic activity, and of the twelve derived from renieramycins, all showed considerable cytotoxic activities. The studies used in this research evaluated the cytotoxic effects of aminonitriles with evident anticancer and antimicrobial activity. The importance of evaluating the cytotoxicity of aminonitriles is emphasized, as well as the need for investigative research that explores other evaluation methods in pre-clinical tests that may corroborate the existing findings, with a view to the development of therapies against emerging health problems.